Effects of (SBS) Styrene-ButadieneStyrene on Physical properties of Bitumen - Dr. Abdulbasit Abdul-Aziz Mahmood; Zeina Osama Yahiya (Genius Journals, 2023)
The presence of water in the asphalt structure causes early weakening, leads decline in asphalt sturdiness in light of the loss of connection between total and folio (stripping) and may cause loss of solidarity and strength in admixture. The most common technique to mitigate moisture damage is by using polymer additives mixed with asphalt binder. The physical characteristics of bitumen are affected by the amount of StyreneButadiene-Styrene (SBS) used, with a five percent addition reducing penetration by 27.5% and a five percent addition increasing the softening point and viscosity by 32.35% and 25.4%, respectively. While when employing SBS, the elongation rises by more than 100. High temperatures are the main factor affecting roads, and using SBS additive causes the road resistance to heat to rise. As a result, when using 5% of SBS, the resistance to flash point and fire point increases by 19.4 and 20.4, respectively, while the elasticity is increased by 20%. The use of polymer SBS is important because it leads to reducing pressure and increasing ductility and resistance to temperatures and it has an effect on the physical and chemical properties. The ratios range from 4-5% of the best ratios to increase the life of the road and reduce the effect of high temperature. The ratio of 4% is better in the northern and central regions because the temperature it does not exceed 76C°, and it is more economical in terms of cost, while the percentage is 5% and higher for the southern regions, since temperatures are more than 76C°.
Keywords: Styrene-Butadiene-Styrene; physical properties